THE ILLNESS OF ADULTS BY CANCER AND THE IMPACT ON THE FAMILY: A LITERATURE REVIEW - Mathias, Caroline Vieira; Girardon-Perlini, Nara Marilene Oliveira; Mistura, Claudelí; Jacobi, Caren da Silva; Stamm, Bruna (Journal of Health Care, 2015)
Introduction: Cancer changes the lives of patients and their families, and there is significant influence ofthe family on health, well-being of each member and on diseases that affect them. Objective: To identifyin literature scientific papers about the impact on the family when one of its members falls ill adult cancer.Methods: A narrative review, conducted in June 2012, the databases of the Latin American and CaribbeanLiterature on Health Sciences (LILACS); Database of Nursing (BDENF), and Medical Literature Analysisand Retrieval System (MEDLINE), with the descriptors "família" or "relações familiares" and "neoplasias".The corpus of the study consisted of 16 items. Results: The impact of having one of the adult memberson a family with cancer begins with the diagnosis of the disease, causing many feelings, which interferespositively or negatively on family relationships. It was also felt that in general, after the cancer diagnosis,the union and the relationship between family members increases, becoming a source of support, securityand emotional stability, which, in a way, collaborates to alleviate suffering. Conclusion: The negativeeffects, such as feelings arising of diagnostic confirmation, configure as possible causes for the lack ofcommunication between family members. The positive repercussions, such as the consolidation of familyrelationship and support of members can contribute to the development of strategies to try to reorganizeand keep the family structure.
Keywords: Family; family relations; neoplasms; nursing.